Biogeografia das espécies invasoras da herpetofauna: influência de dispersores artificiais e fatores ambientais - Parreira, Caroline Nunes (2023)
The colonization of invasive species can impact biodiversity, human well-being, health and the economy. For a species to become invasive, it must overcome biogeographical, physiological and biotic filters, therefore, the understanding of distribution patterns of introduced species is essential to support studies and preventive measures regarding the advance of bioinvasions. The present study aimed to estimate the areas of climatic suitability in Brazil, of the introduced herpetofauna species with high expansion potential, the anuran Eleutherodactylus johnstonei (Amphibia, Eleutherodactylidae) and the lizard Anolis porcatus (Reptilia, Dactyloidae), to evaluate the possible niche overlap with phylogenetically related species that are native to Brazil, and to verify which Brazilian ports are more susceptible to the introduction of Anolis porcatus, a species introduced due maritime trade. The species disitribution models (SDMs) showed that the bioclimatic variables related to temperature had the highest contributions in the model of Anolis porcatus and precipitation had the highest contributions in the model of Eleutherodactylus johnstonei, demonstrating the relationship between the distribution and the habits and characteristics of each of their respective groups. The areas where the exotic populations of these two species occur in Brazil are located in areas of minimum and low climatic suitability, according to the results of SDM. However, Anolis porcatus is rapidly expanding its distribution under these conditions, and its colonization may be more effective and accelerated when that species finds areas of higher climatic suitability. The area of endemicity results identified endemism areas of native species that overlap the areas of climatic suitability of Anolis porcatus and Eleutherodactylus johnstonei obtained with the SDM, suggesting possible future niche overlaps. The present study also found that ports of Salvador, Rio de Janeiro, Santos and Itapoá are more susceptible to new introductions of Anolis porcatus due maritime trades. Both introduced species can expand their distribution to areas where there are phylogenetically close native species and species with similar habits, and there may occur impacts on native species, which demonstrates the importance of studies about the biological interactions of these species, in addition to efforts to obtain a higher knowledge of its areas of occurrence. For Anolis porcatus, the importance of studies in port areas and its surroundings is highlighted, besides the implementation of measures within the scope of port management to prevent new introductions.